2000
DOI: 10.1091/mbc.11.10.3589
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Coupling of the Transmembrane and Kinase Domains of the Neu Receptor Tyrosine Kinase

Abstract: Ligand binding to receptor tyrosine kinases (RTKs) regulates receptor dimerization and activation of the kinase domain. To examine the role of the transmembrane domain in regulation of RTK activation, we have exploited a simplified transmembrane motif, [VVVEVVV] n , previously shown to activate the Neu receptor. Here we demonstrate rotational linkage of the transmembrane domain with the kinase domain, as evidenced by a periodic activation of Neu as the dimerization motif is shifted across the transmembrane do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 51 publications
9
132
1
1
Order By: Relevance
“…Single and multiple tyrosine mutations in the TACC3 region (Y798F, Y853F, Y867F, Y878F) were introduced by PCR-based site-directed mutagenesis. DNA constructs were subcloned into pLXSN vector (10) for focus, proliferation, and 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. All clones were confirmed by DNA sequencing.…”
Section: Dna Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single and multiple tyrosine mutations in the TACC3 region (Y798F, Y853F, Y867F, Y878F) were introduced by PCR-based site-directed mutagenesis. DNA constructs were subcloned into pLXSN vector (10) for focus, proliferation, and 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. All clones were confirmed by DNA sequencing.…”
Section: Dna Constructsmentioning
confidence: 99%
“…Bradford assay or Lowry assay was used to measure total protein concentration. Antibodies were added to lysates for overnight incubation at 4 C with rocking, followed by immunoprecipitation, as described previously (10). Samples were separated by 10% or 12.5% SDS-PAGE and transferred to Immobilon-P membranes (Millipore).…”
Section: Transfection Immunoprecipitation and Immunoblot Analysismentioning
confidence: 99%
“…Bell et al (62) have observed that the activation of an RTK occurs only for a specific TM dimer interface. The rotation of the dimer interface leads to periodic oscillations in kinase activity.…”
Section: Structural Link Between the Tm And The Catalytic Domainsmentioning
confidence: 99%
“…of at least three separate experiments. Oncogenic Neu (NeuNT), activated by the Val664Glu mutation, served as the positive control (set at 100%) (Bell et al, 2000). The transforming activities of ptc1 and ptc1-Q688X constructs are presented as percentages with respect to the positive control.…”
Section: Focus Assaysmentioning
confidence: 99%